Inclusion of Tithonia diversifolia on the quality of Cuba OM22 and Musa sp. - Rodríguez-Badilla, Brayan (2022)
The objective of this study was to determine the effect of the inclusion of Tithonia diversifolia on the physical, fermentative, and nutritional characteristics of Cuba OM22 grass with Musa sp. silage. The study was carried out between September 2020 and July 2021. An unrestricted, randomized design was used to mix Cuba OM22 grass and wild sunflower (Tithonia diversifolia) in percentage ratios of 0:100, 25:75, 50:50, 75:25, and 100:0. 10% of Musa sp. and 5% of molasses were added on a fresh basis to these previous mixtures. The silage was prepared in a 5 kg plastic bag of microsilos with hermetic closure for 60 days. T. diversifolia forage affected the physical characteristics of the silage, mainly color, and texture, while pH was not different between the treatments. The concentration of dry matter decreased as well as the neutral detergent fiber (NDF) and the digestible neutral detergent fiber (dFDN). On the other hand, T. diversifolia increased the contents of crude protein (PC) and non-fibrous carbohydrates (NFC). PC raises 0.5 percentage points, while NFC increases 4.25 percentage points, and NDF reduces at a rate of 5.0 points. In all cases, for each increase of 25% of T. diversifolia; those effects were reflected in the increase of the number of digestible nutrients on the silage. In conclusion, the inclusion of T. diversifolia, allowed to improve the nutritional quality of the silages, without affecting the fermentation process, although its physical quality could be affected due to the higher humidity of the shrub utilized.